2014
DOI: 10.1111/1468-5973.12035
|View full text |Cite
|
Sign up to set email alerts
|

On the Need for a Paradigm Shift in the Dutch Command and Information System for the Acute Phase of Disasters

Abstract: By and large, scientists agreed on what should be the output of a good command and information system in the acute phase of a disaster. The public needs fast and accurate information and fast ‘meaning‐making’ if they are to be as self‐reliant as possible and to be in the best possible position to cope with the shock of the disaster. Operational units need decentralized command and sometimes fast strategic decision‐making. Despite this, classical command and information systems such as the three‐tier system req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…This workflow however makes it difficult for the other team members to process and interpret the information, impeding effective information sharing. The main contribution of this paper is that we build upon suggestions in literature (Rimstad et al, 2014;Scholtens et al, 2014;Wolbers and Boersma, 2013) to investigate two possible improvements to this default state: (1) we provide enriched information to the response team, and (2) we centralize information sharing via a coordinator in the team. By means of a controlled experiment, we contrast these two possible improvements to the existing situation and evaluate the impact on the teams' situation awareness.…”
Section: Introductionmentioning
confidence: 99%
“…This workflow however makes it difficult for the other team members to process and interpret the information, impeding effective information sharing. The main contribution of this paper is that we build upon suggestions in literature (Rimstad et al, 2014;Scholtens et al, 2014;Wolbers and Boersma, 2013) to investigate two possible improvements to this default state: (1) we provide enriched information to the response team, and (2) we centralize information sharing via a coordinator in the team. By means of a controlled experiment, we contrast these two possible improvements to the existing situation and evaluate the impact on the teams' situation awareness.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies for crisis communication that is of critical importance. So, when there is no daily routine in sharing information to the general public, there will be predictable shortcomings in the communication during a crisis (Scholtens and others ).…”
Section: Discussionmentioning
confidence: 99%
“…Information sharing is a crucial element in crisis management and a “command and information system” (also abbreviated to “C&I system”) should be part of the crisis management structure in order to manage the actions of all parties concerned, both in physical terms and as regards the provision of information to the public. The following 2 design principles should be part of any C&I system: The C&I system should enable rapid information provision to the general public within no more than 30 min after the crisis occurs. The C&I system should enable meaning making by a public leader within an hour after the beginning of a crisis (Scholtens and others ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without that information, people will still make decisions and judgments, but those decisions will be reasonable and appropriate only from the subjective point of view and will stand up to the viewpoint of experts. Disaster risk management structures come into consideration in cases of residents who are unable to help themselves or cannot be rescued by fellow citizens [23]. In their study, Di Mauro et al [24] showed that people do have an interest in preparation and prevention activities with regard to Seveso facilities, but this is hindered by insufficient risk communication and low awareness about risks.…”
Section: Citizens' Behaviour During Emergency Situationsmentioning
confidence: 99%